PENGEMBANGAN MEDIA GAMBAR BERSERI BERBASIS KEARIFAN LOKAL PADA KETERAMPILAN MENULIS CERITA PENDEK SISWA KELAS V MIN 3 LANGSA - Khairani, Luthfi Mahsa; Mulyahati, Bunga; Maisarah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of students' short story writing skills and the lack of learning media that integrate local wisdom. The study aimed to develop and determine the validity, practicality, and effectiveness of local wisdom-based serial picture media for improving the short story writing skills of fifth-grade students at MIN 3 Langsa. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were 12 fifth-grade students at MIN 3 Langsa. Data were collected through validation questionnaires completed by material, media, and language experts, teacher and student response questionnaires, and an assessment of students' short story writing skills. The results showed that the material expert validation reached 90.9% (very valid), the media expert validation reached 80% (valid), and the language expert validation reached 98.33% (very valid), resulting in an overall validity score of 89.74%, which falls into the very valid category. The practicality test showed that student responses reached 91.66% and teacher responses reached 90%, with an average practicality score of 91.33%, categorized as very practical. Furthermore, the effectiveness test yielded an N-Gain score of 0.64, indicating a moderate level of effectiveness. Therefore, the developed local wisdom-based serial picture media is considered very valid, very practical, and moderately effective, making it suitable for use in Indonesian language learning, particularly in teaching short story writing to fifth-grade students at MIN 3 Langsa.